Quantum dots, quantum dot precursors, and methods for producing quantum dots

A low-temperature metal replacement method for synthesizing cadmium-zinc-selenium-sulfur quantum dots addresses safety and scalability issues in cadmium-based quantum dot production, achieving narrow fluorescence and high quantum yield for mass production with adjustable wavelengths.

JP7622356B2Active Publication Date: 2025-01-28TOPPAN HOLDINGS INC
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
JP2020089822
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2020-05-22
Publication Date
2025-01-28
Estimated Expiration
2040-05-22

AI Technical Summary

Technical Problem

Existing methods for synthesizing cadmium-based quantum dots with narrow fluorescence half-width and high quantum yield are unsafe and not suitable for mass production, particularly due to high-temperature reactions with hazardous reagents.

Method used

A low-temperature metal replacement method using organic and inorganic copper and zinc compounds to synthesize cadmium-zinc-selenium-sulfur quantum dots, controlling the molar ratios to achieve a fluorescence half-width of 35 nm or less and a quantum yield of 10% or more, allowing for safe and mass production.

Benefits of technology

The method enables the production of cadmium-based quantum dots with narrow fluorescence and high color gamut, ensuring safety and scalability, with adjustable fluorescence wavelengths from 400 to 700 nm.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007622356000002
    Figure 0007622356000002
  • Figure 0007622356000003
    Figure 0007622356000003
  • Figure 0007622356000004
    Figure 0007622356000004
Patent Text Reader

Abstract

To provide a quantum dot that emits blue to red fluorescence having a narrow fluorescence half value width that is safe and can be mass-produced, by using a metal exchange method that can synthesize at low temperature.SOLUTION: A quantum dot (1) of the invention contains cadmium (Cd) and selenium (Se), or cadmium (Cd), zinc (Zn), and selenium (Se), or cadmium (Cd), zinc (Zn), selenium (Se) and sulfur (S), or cadmium (Cd), zinc (Zn) and sulfur and has a fluorescence half value width of 35 nm or smaller. An average particle size of the quantum dot is preferably in the range of 2 nm or larger and 10 nm or smaller.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to quantum dots, quantum dot precursors, and methods for producing quantum dots. [Background technology]

[0002] Quantum dots are nanoparticles composed of hundreds to thousands of atoms and having a particle size of several nm to several tens of nm. Quantum dots are also called fluorescent nanoparticles, semiconductor nanoparticles, or nanocrystals. Quantum dots have the characteristic that the emission wavelength can be changed in various ways depending on the particle size and composition of the nanoparticles.

[0003] The performance of quantum dots is expressed by the fluorescence quantum yield (QY) and the fluorescence full width at half maximum (FWHM). When quantum dots are used as wavelength conversion materials in the visible light region, their most significant feature is the wide range of colors that can be expressed, that is, a wide color gamut. In order to achieve a wide color gamut using quantum dots, it is important to narrow the fluorescence full width at half maximum.

[0004] Representative materials for green or red quantum dots with high fluorescence quantum yield and narrow fluorescence half-width include cadmium selenide (CdSe) quantum dots using cadmium (Cd), or ZnCdSeS, which is a four-element solid solution of this quantum dot with zinc (Zn) or sulfur (S).

[0005] For example, in Non-Patent Document 1, quantum dots of CuSe consisting of a copper (Cu) and selenium (Se) compound are synthesized, and then metal-exchanged with zinc (Zn) or cadmium (Cd) to obtain quantum dots of ZnSe or CdSe. However, there is no report showing good luminescence properties by the metal-exchange method. [Prior art documents] [Non-patent literature]

[0006] [Non-Patent Document 1] J.Am.Chem.Soc.(2015)137 29 9315-9323 Summary of the Invention [Problem to be solved by the invention]

[0007] As described above, although research and development of Cd-based quantum dots is progressing, no Cd-based quantum dots have been reported that have been produced using the metal exchange method (cation exchange method) and have luminescence characteristics of a fluorescence wavelength of 400 to 800 nm and a fluorescence half-width of 35 nm or less.

[0008] The present invention has been made in consideration of the above-mentioned points, and aims to provide a method for mass-producing Cd-based quantum dots that are highly safe and can be produced using Cd-based quantum dots with narrow fluorescence half-widths, quantum dot precursors, and a metal exchange method that enables synthesis at low temperatures. [Means for solving the problem]

[0011] The method for producing quantum dots in the present invention includes synthesizing CuSe or CuSeS as a precursor from an organic copper compound or an inorganic copper compound and an organic chalcogen compound, simultaneously adding a zinc compound and a cadmium compound to exchange the copper of CuSe or CuSeS with the cadmium and zinc, The Zn / Cd molar ratio is 10 to 20. CdZnSe, or The Zn / Cd molar ratio is 10 or more and 20 or less, and the S / Se molar ratio is greater than 0 and less than 0.2. The method is characterized by synthesizing a quantum dot core made of CdZnSeS, having a fluorescence half-width of 35 nm or less, and an average particle size of 2 nm to 10 nm. Effect of the Invention

[0012] According to the Cd-based quantum dots of the present invention, the fluorescence half-width can be narrowed, and an improvement in the wide color gamut can be achieved.

[0013] Furthermore, according to the method for producing quantum dots of the present invention, it is possible to safely produce Cd-based quantum dots with narrow fluorescence half-widths in a manner that allows for mass production. [Brief description of the drawings]

[0014] [Figure 1] Fig. 1A is a schematic diagram of a quantum dot according to an embodiment of the present invention, and Fig. 1B is a schematic diagram of a quantum dot according to an embodiment of the present invention different from that of Fig. 1A. [Diagram 2] 1 is a photoluminescence (PL) spectrum of CdSe in Example 1. [Diagram 3] 1 shows a PL spectrum of ZnCdSe in Example 2. [Figure 4] 1 shows a PL spectrum of ZnCdSe in Example 3. [Diagram 5] 1 shows a PL spectrum of ZnCdSe in Example 4. [Figure 6] 1 is a PL spectrum of ZnCdSeS in Example 5. [Figure 7] 1 is an X-ray diffraction (XRD) spectrum of CdSe in Example 1. [Figure 8] 1 is an XRD spectrum of ZnCdSe in Example 2. [Figure 9] 1 is an XRD spectrum of ZnCdSe in Example 3. [Figure 10] 1 is an XRD spectrum of ZnCdSe in Example 4. [Figure 11] 1 is an XRD spectrum of ZnCdSeS in Example 5. [Figure 12] 1 is a scanning electron microscopy (SEM) photograph of CdSe in Example 1. [Figure 13] 1 is a SEM photograph of ZnCdSe in Example 2. [Figure 14] 1 is a SEM photograph of ZnCdSe in Example 3. [Figure 15] 1 is a SEM photograph of ZnCdSe in Example 4. [Figure 16] 1 is a SEM photograph of ZnCdSeS in Example 5. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0015] In recent years, research and development of Cd-based quantum dots has progressed. Conventionally, most syntheses involve direct reaction of each raw material. Direct synthesis methods include synthesis at high temperatures or synthesis using organic zinc compounds such as diethylzinc (Et2Zn) to increase reactivity. However, even when synthesis is performed at high temperatures or highly reactive reagents such as diethylzinc are used, there is a risk of heat generation or fire during the reaction. Therefore, from a safety standpoint, it is not suitable for mass production.

[0016] Therefore, the present inventors have developed Cd-based quantum dots that have a narrow fluorescence half-width and emit blue to red fluorescence by using a cation exchange method that allows synthesis at low temperatures. In addition, the present inventors have made it possible to synthesize the quantum dots in a mass-production manner with high safety.

[0017] An embodiment of the present invention (hereinafter, abbreviated as "embodiment") will be described in detail below. Note that the present invention is not limited to the following embodiment, and can be practiced with various modifications within the scope of the gist. In addition, the notation "to" includes both the lower limit and the upper limit as a range.

[0018] 1A and 1B are schematic diagrams of quantum dots in this embodiment.

[0019] The quantum dot 1 shown in FIG. 1A is a nanocrystal containing cadmium (Cd) and selenium (Se), or cadmium (Cd), zinc (Zn) and selenium (Se), or cadmium (Cd), zinc (Zn), selenium (Se) and sulfur (S), or cadmium (Cd), zinc (Zn) and sulfur (S).

[0020] The quantum dot 1 has fluorescent properties due to band edge emission, and exhibits a quantum size effect due to its nano-sized particles.

[0021] Here, the term "nanocrystal" refers to nanoparticles having a particle size of about several nm to several tens of nm. In this embodiment, a large number of quantum dots 1 can be produced with a substantially uniform particle size.

[0022] The quantum dots 1 contain Cd and Zn, or Cd, Zn and Se, or Cd, Zn, Se and S, or Cd, Zn and S as the main components, but may contain elements other than these elements.

[0023] The quantum dot 1 of this embodiment has a fluorescence half-width of 35 nm or less. The "fluorescence half-width" refers to the full width at half maximum, which indicates the spread of the fluorescence wavelength at half the intensity of the peak value of the fluorescence intensity in the fluorescence spectrum. The fluorescence half-width is preferably 32 nm or less. The fluorescence half-width is more preferably 30 nm or less. The fluorescence half-width is even more preferably 25 nm or less. The fluorescence half-width is even more preferably 20 nm or less. In this way, in this embodiment, the fluorescence half-width can be narrowed, thereby improving the color gamut.

[0024] In this embodiment, as described later, the quantum dots 1 are synthesized as a reaction system in which copper chalcogenide is used as a precursor, and then a metal exchange reaction (cation exchange reaction) is performed on the precursor. By producing the quantum dots 1 based on such an indirect synthesis reaction, the fluorescence half-width can be narrowed, and specifically, a fluorescence half-width of 35 nm or less can be achieved.

[0025] It is preferable that a large number of organic ligands 2 are coordinated to the surface of the quantum dots 1. This makes it possible to suppress the aggregation of the quantum dots 1, and to develop the desired optical properties. There is no particular limitation on the ligands that can be used in the reaction, but the following ligands are representative examples.

[0026] (1) Aliphatic primary amines Oleylamine: C 18 H 35NH2, stearyl(octadecyl)amine: C 18 H 37 NH2, dodecyl(lauryl)amine: C 12 H 25 NH2, Decylamine: C 10 H 21 NH2, Octylamine: C8H 17 NH2 (2) Fatty acid type Oleic acid: C 17 H 33 COOH, stearic acid: C 17 H 35 COOH, Palmitic acid: C 15 H 31 COOH, myristic acid: C 13 H 27 COOH, lauryl(dodecanoic) acid: C 11 H 23 COOH, Decanoic acid: C9H 19 COOH, Octanoic acid: C7H 15 COOH (3) Thiols Octadecanethiol: C 18 H 37 SH, hexanedecanethiol: C 16 H 33 SH, tetradecanethiol: C 14 H 29 SH, dodecanethiol: C 12 H 25 SH, decanethiol: C 10 H 21 SH, Octanethiol: C8H 17 SH (4) Phosphine Trioctylphosphine: (C8H 17 )3P, triphenylphosphine: (C6H5)3P, tributylphosphine: (C4H9)3P (5) Phosphine oxides Trioctylphosphine oxide: (C8H 17 )3P=O, triphenylphosphine oxide: (C6H5)3P=O, tributylphosphine oxide f: (C4H9)3P=O

[0027] The quantum dot 1 in this embodiment has a fluorescence quantum yield of 10% or more. The fluorescence quantum yield is more preferably 30% or more, and even more preferably 50% or more. In this manner, the quantum dot 1 can have an increased fluorescence quantum yield in this embodiment.

[0028] The average particle size of the quantum dots 1 in this embodiment is 2 nm or more and 10 nm or less. The average particle size of the quantum dots 1 is preferably 3 nm or more and 9 nm or less, and more preferably 4 nm or more and 8 nm or less. The "average particle size" is calculated by calculating the diameters of all particles of 10 or more (preferably 200 or more) as circle equivalent diameters, and the average value is taken as the particle size.

[0029] In addition, the particle size of the quantum dots 1 in this embodiment is preferably within the range of ±2 nm of the average particle size. In this manner, in this embodiment, a large number of quantum dots 1 can be produced with extremely uniform particle sizes.

[0030] In this embodiment, the fluorescence wavelength can be freely controlled to about 400 nm or more and 700 nm or less. The quantum dots 1 in this embodiment are solid solutions based on ZnCdSeS using chalcogen elements. In this embodiment, the fluorescence wavelength can be controlled by adjusting the particle size of the quantum dots 1 and the composition of the quantum dots 1. In this embodiment, the fluorescence wavelength can be set to 450 nm or more. In this embodiment, the fluorescence wavelength can be controlled to blue to red.

[0031] The quantum dot 1 shown in Fig. 1B has a core-shell structure having a core 1a and a shell 1b coated on the surface of the core 1a. As shown in Fig. 1B, it is preferable that a large number of organic ligands 2 are coordinated to the surface of the quantum dot 1.

[0032] The core 1a of the quantum dot 1 shown in Fig. 1B is the nanocrystal shown in Fig. 1A. Therefore, the core 1a is preferably formed of Cd and Se, Cd, Zn and Se, or Cd, Zn, Se and S, or Cd, Zn and S. The shell 1b may be made of any material, but may be made of zinc sulfide (ZnS), for example.

[0033] The shell 1b may be in a state of being solidified on the surface of the core 1a. In FIG. 1B, the boundary between the core 1a and the shell 1b is shown by a dotted line, but this means that the boundary between the core 1a and the shell 1b may or may not be confirmed by analysis. In this embodiment, the core alone having Cd and Se, Cd, Zn and Se, Cd, Zn, Se and S, or Cd, Zn and S has the characteristic of emitting fluorescence.

[0034] The quantum dot 1 shown in FIG. 1B can also have a fluorescence half-width of 32 nm or less, similar to that of FIG. 1A. The fluorescence half-width is more preferably 25 nm or less. The fluorescence wavelength can be freely controlled to be in the range of 400 nm or more and 700 nm or less. In this embodiment, the fluorescence wavelength can be controlled to be blue.

[0035] Next, a method for producing the quantum dot 1 of this embodiment will be described. First, in this embodiment, a copper chalcogenide (precursor) is synthesized from an organic copper compound or an inorganic copper compound and an organic chalcogen compound. Specifically, the precursor is preferably copper selenide: Cu2Se or copper selenide sulfide: Cu2SeS.

[0036] Here, in this embodiment, the Cu raw material of Cu2Se is not particularly limited, but for example, the following organic copper reagents or inorganic copper reagents can be used. That is, as acetates, copper acetate (I) Cu(OAc) and copper acetate (II): Cu(OAc)2, as fatty acid salts, copper stearate: Cu(OC(=O)C 17 H 35 )2, Copper oleate: Cu(OC(=O)C 17 H 33)2, Copper myristate: Cu(OC(=O)C 13 H 27 )2, Copper dodecanoate: Cu(OC(=O)C 11 H 23 )2, copper acetylacetonate: Cu(acac)2, and both monovalent and divalent halides can be used, such as copper chloride(I): CuCl, copper chloride(II): CuCl2, copper bromide(I): CuBr, copper bromide(II): CuBr2, copper iodide(I): CuI, and copper iodide(II): CuI2.

[0037] In this embodiment, selenium is used as a raw material in the form of an organic selenium compound (organic chalcogenide). In particular, a solution in which selenium is dissolved in a mixture of oleylamine and dodecanethiol (Se-DDT / OLAm) exhibits good luminescence characteristics after cation exchange. In addition, trioctylphosphine selenide: (C8H) is obtained by dissolving sulfur in a high-boiling point solvent that is a long-chain phosphine-based hydrocarbon such as trioctylphosphine. 17 )3P=Se, or tributylphosphine selenide: (C4H9)3P=Se, in which selenium is dissolved in tributylphosphine, can be used. Alternatively, a solution in which selenium is dissolved at high temperature in a high-boiling solvent that is a long-chain hydrocarbon such as octadecene (Se-ODE) can be used.

[0038] In this embodiment, an organic copper compound or an inorganic copper compound is mixed with an organic chalcogen compound and dissolved. As a solvent, octadecene can be used as a high boiling point saturated hydrocarbon or unsaturated hydrocarbon. In addition, t-butylbenzene can be used as an aromatic high boiling point solvent, butyl butyrate: C4H9COOC4H9, benzyl butyrate: C6H5CH2COOC4H9, etc. can be used as a high boiling point ester solvent, but it is also possible to use an aliphatic amine-based or fatty acid-based compound, an aliphatic phosphorus-based compound, or a mixture of these as a solvent.

[0039] At this time, the copper chalcogenide (precursor) is synthesized at a reaction temperature set in the range of 120° C. to 250° C. Note that the reaction temperature is preferably lower, 120° C. to 200° C., and more preferably lower, 120° C. to 150° C.

[0040] In this embodiment, the reaction method is not particularly limited, but in order to obtain quantum dots with a narrow fluorescence half-width, it is important to synthesize Cu2Se and Cu2SeS with uniform particle size. For example, in this embodiment, it is preferable that the particle size of the copper chalcogenide (precursor) is uniform within a range of ±2 nm of the average particle size. The definition of the average particle size is as described above.

[0041] The sulfur (S) used in the synthesis of Cu2SeS can be a solution (S-TOP) in which sulfur is dissolved in a high-boiling solvent that is a thiol or a long-chain phosphine-based hydrocarbon such as trioctylphosphine, a solution (S-ODE) in which sulfur is dissolved in a high-boiling solvent that is a long-chain hydrocarbon such as octadecene, or a solution (S-DDT / OLAm) in which sulfur is dissolved in a mixture of oleylamine and dodecanethiol. The thiol is not particularly limited, but for example, octadecanethiol:C 18 H 37 SH, hexanedecanethiol: C 16 H 33 SH, tetradecanethiol: C 14 H 29 SH, dodecanethiol: C 12 H 25 SH, decanethiol: C 10 H 21 SH, Octanethiol: C8H 17 SH, benzenethiol: C6H5SH, etc.

[0042] In this embodiment, the fluorescence wavelength can be freely controlled in the range of 400 nm to 700 nm while maintaining the fluorescence half-width of 32 nm or less of the quantum dots by changing the addition ratio of selenium and sulfur, which are anion species used in the synthesis of the copper chalcogenide precursor. Even if the particle size and cationic species (Zn or Cd) are the same, if the S ratio of the precursor is high, the wavelength will be short. Specifically, the target wavelength can be targeted by controlling the molar ratio of sulfur to selenium (S / Se). In this embodiment, the target wavelength is mainly 450 to 550 nm, and good results are obtained by adjusting S / Se<0.2. Here, the molar ratio includes 0, and in this case, the quantum dots do not contain sulfur. By adjusting the molar ratio of sulfur to selenium in the range of more than 0 and less than 0.2, the quantum dots can contain both selenium and sulfur.

[0043] Next, an organic zinc compound or an inorganic zinc compound is prepared as a raw material for ZnCdSe or ZnCdSeS. The organic zinc compound or the inorganic zinc compound is a raw material that is stable in air and easy to handle. Although the structure of the organic zinc compound or the inorganic zinc compound is not particularly limited, it is preferable to use a zinc compound with high ionicity in order to efficiently carry out the metal exchange reaction. For example, the organic zinc compound and the inorganic zinc compound shown below can be used.

[0044] The zinc raw materials are zinc acetate: Zn(OAc)2, zinc nitrate: Zn(NO3)2 as acetate salts, and zinc stearate: Zn(OC(=O)C 17 H 35 )2, Zinc oleate: Zn(OC(=O)C 17 H 33 )2, Zinc palmitate: Zn(OC(=O)C 15 H 31 )2, Zinc myristate: Zn(OC(=O)C 13 H 27 )2, Zinc dodecanoate: Zn(OC(=O)C 11 H 23)2, zinc acetylacetonate: Zn(acac)2, and as halides, zinc chloride: ZnCl2, zinc bromide: ZnBr2, zinc iodide: ZnI2, and as zinc carbamates, zinc diethyldithiocarbamate: Zn(SC(=S)N(C2H5)2)2, zinc dimethyldithiocarbamate: Zn(SC(=S)N(CH3)2)2, zinc dibutyldithiocarbamate: Zn(SC(=S)N(C4H9)2)2, etc. can be used.

[0045] Cadmium raw materials include acetate salts such as cadmium acetate: Cd(OAc)2, cadmium nitrate: Cd(NO3)2, and fatty acid salts such as cadmium stearate: Cd(OC(=O)C 17 H 35 )2, Cadmium oleate: Cd(OC(=O)C 17 H 33 )2, Cadmium palmitate: Cd(OC(=O)C 15 H 31 )2, Cadmium myristate: Cd(OC(=O)C 13 H 27 )2, Cadmium dodecanoate: Cd(OC(=O)C 11 H 23 )2, cadmium acetylacetonate: Cd(acac)2, and as halides, cadmium chloride: CdCl2, cadmium bromide: CdBr2, cadmium iodide: CdI2, and as cadmium carbamates, cadmium diethyldithiocarbamate: Cd(SC(=S)N(C2H5)2)2, cadmium dimethyldithiocarbamate: Cd(SC(=S)N(CH3)2)2, and cadmium dibutyldithiocarbamate: Cd(SC(=S)N(C4H9)2)2, etc. can be used.

[0046] Next, the organic zinc compound or inorganic zinc compound is added to the reaction solution in which the precursor of copper chalcogenide is synthesized. This causes a metal exchange reaction between copper (Cu) of copper chalcogenide and zinc (Zn) and cadmium (Cd). The metal exchange reaction is preferably caused at a temperature of 140°C or higher and 300°C or lower. It is more preferable to cause the metal exchange reaction at a lower temperature, 140°C or higher and 240°C or lower, and even more preferable to cause the metal exchange reaction at a lower temperature, 140°C or higher and 180°C or lower.

[0047] In this embodiment, the metal exchange reaction between Cu and Zn and Cd proceeds quantitatively. If the precursor Cu remains in the nanocrystal, it acts as a dopant and emits light by a different emission mechanism, widening the fluorescence half-width. Therefore, it is preferable that the precursor Cu is not contained in the nanocrystal. However, by using a precursor such as CuSe, particles with a better shape and a more uniform particle size than the conventional directly synthesized ZnCdSe can be obtained. In addition, by checking the remaining Cu, it is possible to judge whether or not this method has been used. The amount of remaining Cu is measured by ICP (inductively coupled plasma) emission spectroscopy.

[0048] In addition, the above describes the metal exchange reaction between Cu and Zn and between Cu and Cd. However, it is possible to generate quantum dots 1 containing Cd and Se by metal exchange between Cu and Cd.

[0049] In this embodiment, when metal exchange is carried out, a compound having an auxiliary role of liberating the precursor metal into the reaction solution by coordination or chelation is necessary.

[0050] The compound having the above-mentioned function is a ligand capable of forming a complex with Cu. For example, phosphorus-based ligands, amine-based ligands, and sulfur-based ligands are preferable, and among them, phosphorus-based ligands are more preferable due to their high efficiency.

[0051] This allows the metal exchange between Cu and Cd, or between Cu and Cd and Zn, to be carried out appropriately, and quantum dots with narrow fluorescence half-widths based on Cd and Se, Zn, Cd and Se, Zn, Cd, Se and S, or Cd, Zn and S can be mass-produced with high safety.

[0052] In addition, in the metal exchange reaction, good characteristics can be obtained by simultaneously exchanging two or more kinds of metal species. Although the metal species is not particularly limited, two or more kinds can be selected and used mainly from Zn, Cd, Mg, Mn, Ag, In, Ga, Al, etc. However, in this embodiment, Cd is an essential element. For example, in this embodiment, if only Cd is metal exchanged in a precursor of copper chalcogenide to synthesize CdSe, and then Zn is added, good luminescence characteristics cannot be obtained (Comparative Example 1). Therefore, it is preferable to add two or more kinds of cationic species (Zn and Cd in this embodiment) at the same time as in this embodiment (Examples 2 to 5).

[0053] In this embodiment, the fluorescence wavelength can be freely controlled in the range of 400 nm to 700 nm while maintaining a fluorescence half-width of 32 nm or less by changing the addition ratio of zinc and cadmium, which are cationic species used during metal exchange. For example, in this embodiment, when ZnCdSe is synthesized with the ratio of the amount of zinc substance to the amount of cadmium substance being in the range of 10 to 20 in the amount of zinc compound and cadmium compound added, it is possible to control the fluorescence wavelength in the range of 450 nm to 600 nm while maintaining a fluorescence half-width of 35 nm or less.

[0054] In this embodiment, in the amount of zinc compound and cadmium compound added, it is preferable to adjust the molar ratio of the amount of zinc substance to the amount of cadmium substance (Zn / Cd) to a range of 30 or less. In this embodiment, the molar ratio = 0 is also included. In this case, zinc is not included in the quantum dots. In addition, when both cadmium and zinc are included in the quantum dots, the molar ratio is preferably 5 to 25, and more preferably 10 to 20 (Examples 2 to 5).

[0055] In this embodiment, quantum dots are synthesized by synthesizing a copper chalcogenide as a precursor from an organic copper compound or an inorganic copper compound and an organic chalcogen compound, and then metal exchange is performed using the precursor. In this way, in this embodiment, quantum dots are synthesized first through the synthesis of a precursor, and are not directly synthesized. Unlike direct synthesis, such indirect synthesis makes it easy to control the reaction rate, and does not require difficult reaction control to obtain a uniform particle size. In addition, indirect synthesis does not require the use of reagents that are too reactive and dangerous to handle, as in direct synthesis. Therefore, compared to direct synthesis, the reaction is easier to control during production, making it possible to safely and stably synthesize CdSe, ZnCdSe, ZnCdS, or ZnCdSeS quantum dots with narrow fluorescence half-widths.

[0056] In this embodiment, it is possible to obtain the desired quantum dots by performing metal exchange of Cu-Zn and Cd in one pot without isolating and purifying the precursor. On the other hand, the precursor copper chalcogenide may be used after being isolated and purified once.

[0057] Furthermore, in this embodiment, the synthesized quantum dots exhibit fluorescent properties without undergoing various treatments such as washing, isolation and purification, coating treatment, and ligand exchange.

[0058] However, as shown in FIG. 1B, the fluorescence quantum yield can be further increased by covering a core 1a made of a nanocrystal such as CdSe, ZnCdSe, ZnCdS, or ZnCdSeS with a shell 1b such as ZnS.

[0059] In addition, in this embodiment, the core / shell structure can be synthesized at the precursor stage. For example, Cu2Se / Cu2S can be synthesized using a precursor copper chalcogenide, and then ZnCdSe / ZnCdS can be obtained by metal exchange of Cu-Zn and Cd.

[0060] In the present embodiment, the S raw material used for the shell structure is not particularly limited, but the following raw materials are typical examples.

[0061] Thiols: Octadecanethiol: C 18 H 37 SH, hexanedecanethiol: C 16 H 33 SH, tetradecanethiol: C 14 H 29 SH, dodecanethiol: C 12 H 25 SH, decanethiol: C 10 H 21 SH, Octanethiol: C8H 17 Examples of solvents that can be used include sulfur dissolved in a high-boiling solvent such as SH, benzenethiol: CHSH, or a long-chain phosphine-based hydrocarbon such as trioctylphosphine (S-TOP), a solution of sulfur dissolved in a high-boiling solvent such as octadecene (S-ODE), or a solution of sulfur dissolved in a mixture of oleylamine and dodecanethiol (S-DDT / OLAm).

[0062] The applications of the quantum dots 1 shown in Figures 1A and 1B are not particularly limited. For example, the quantum dots 1 of this embodiment that emit blue fluorescence can be applied to wavelength conversion members, lighting members, backlight devices, display devices, and the like.

[0063] The quantum dot 1 of this embodiment is applied to a part of a wavelength conversion member, an illumination member, a backlight device, a display device, etc., and when, for example, photoluminescence (PL) is adopted as the light emission principle, it is possible to emit blue fluorescence by UV irradiation from a light source. Alternatively, when electroluminescence (EL) is adopted as the light emission principle, or when all three primary colors are emitted by quantum dots by other methods, it is possible to make a light emitting element that emits blue fluorescence using the quantum dot 1 of this embodiment. In this embodiment, it is possible to emit white light by making a light emitting element (full color LED) that includes the quantum dot 1 of this embodiment that emits blue fluorescence, together with the quantum dot that emits green fluorescence and the quantum dot that emits red fluorescence.

[0064] The wavelength conversion member is formed in a sheet, film, or molded body. For example, a molded body in which quantum dots are dispersed in a resin is stored in a container having a storage space by pressing or the like. At this time, it is preferable that the refractive index of the molded body is smaller than the refractive index of the container. As a result, a part of the light that enters the molded body is totally reflected by the inner wall of the container. Therefore, the amount of light leaking to the outside from the side of the container can be reduced. By applying the quantum dots with a narrow fluorescence half-width in this embodiment to wavelength conversion members, lighting members, backlight devices, display devices, and the like, it is possible to effectively improve the light emission characteristics. EXAMPLES

[0065] The effects of the present invention will be described below with reference to examples and comparative examples, but the present invention is not limited to the following examples.

[0066] <Raw materials> In the present invention, the following raw materials were used to synthesize quantum dots. <Solvent> Octadecene: Idemitsu Kosan Co., Ltd.: Linearene (registered trademark) 18 Oleylamine: Kao Corporation: Farmin (registered trademark) OV Trioctylphosphine: manufactured by Hokko Chemical Co., Ltd. Dodecanethiol: manufactured by Kao Corporation: Thiokalcol (registered trademark), or manufactured by Aldrich Co., Ltd. <Metal> Anhydrous copper(II) acetate: Fujifilm Wako Pure Chemical Industries, Ltd. Zinc chloride: Kishida Chemical Co., Ltd. Cadmium acetate dihydrate: manufactured by Ikoma Chemical Co., Ltd. Selenium (4N: 99.99%): Shinko Chemical Industry Co., Ltd. Sulfur: Kishida Chemical Co., Ltd. <Measuring equipment> Fluorescence spectrometer: JASCO F-2700 UV-Visible spectrophotometer: Hitachi V-770 Quantum yield measurement device: Otsuka Electronics Co., Ltd. QE-1100 X-ray diffraction device (XRD): Bruker D2 PHASER Scanning electron microscope (SEM): Hitachi SU9000

[0067] [Example 1] 91 mg of anhydrous copper acetate (Cu(OAc)2), 4.8 mL of oleylamine (OLAm), and 7.75 mL of octadecene (ODE) were placed in a 100 mL reaction vessel, and the mixture was heated at 150°C for 5 minutes under an inert gas (N2) atmosphere with stirring to dissolve the raw materials.

[0068] To this solution, 1.4 mL of a 0.285 M solution obtained by dissolving selenium (Se) powder in dodecanethiol (DDT) and oleylamine (OLAm) was added, and the mixture was heated with stirring at 150° C. for 10 minutes. The resulting reaction solution was cooled to room temperature.

[0069] Then, 986 mg of cadmium acetate dihydrate (Cd(OAc)2·2H2O), 10 mL of trioctylphosphine (TOP), and 0.4 mL of oleylamine (OLAm) were added, and the mixture was heated with stirring at 180°C for 10 minutes under an inert gas (N2) atmosphere. The resulting reaction solution was cooled to room temperature.

[0070] Toluene and ethanol were added to this reaction solution to generate a precipitate, which was then centrifuged to recover the precipitate, and 12 mL of octadecene (ODE) was added to disperse the precipitate.

[0071] Then, 986 mg of cadmium acetate dihydrate (Cd(OAc)2·2H2O), 5 mL of trioctylphosphine (TOP), and 0.5 mL of oleylamine (OLAm) were added and heated with stirring at 180°C for 10 minutes under an inert gas (N2) atmosphere. The resulting reaction solution was cooled to room temperature. This resulted in the production of CdSe quantum dots in the reaction solution.

[0072] The reaction solution was measured using a fluorescence spectrometer and a quantum efficiency measurement system. As a result, as shown in Figure 2, the optical characteristics were obtained, with a fluorescence wavelength of about 670 nm and a fluorescence half-width of about 32 nm.

[0073] The reaction solution was measured using an XRD device. The results are shown in Figure 7. A scanning electron microscope (SEM) photograph of the reaction solution is shown in Figure 12. The average particle size was found to be 6.1 nm.

[0074] [Example 2] 91 mg of anhydrous copper acetate (Cu(OAc)2), 4.8 mL of oleylamine (OLAm), and 7.75 mL of octadecene (ODE) were placed in a 100 mL reaction vessel, and the mixture was heated at 150°C for 5 minutes under an inert gas (N2) atmosphere with stirring to dissolve the raw materials.

[0075] To this solution, 1.4 mL of a 0.285 M solution obtained by dissolving selenium (Se) powder in dodecanethiol (DDT) and oleylamine (OLAm) was added, and the mixture was heated with stirring at 150° C. for 10 minutes. The resulting reaction solution was cooled to room temperature.

[0076] Then, 504 mg of zinc chloride (ZnCl2), 98.6 mg of cadmium acetate dihydrate (Cd(OAc)2·2H2O), 10 mL of trioctylphosphine (TOP), and 0.4 mL of oleylamine (OLAm) were added and heated with stirring at 180°C for 30 minutes under an inert gas (N2) atmosphere. The resulting reaction solution was cooled to room temperature.

[0077] Toluene and ethanol were added to this reaction solution to generate a precipitate, which was then centrifuged to recover the precipitate, and 12 ml of octadecene (ODE) was added to disperse the precipitate.

[0078] Then, 504 mg of zinc chloride (ZnCl2), 5 mL of trioctylphosphine (TOP), and 0.5 mL of oleylamine (OLAm) were added, and the mixture was heated under inert gas (N2) atmosphere at 180°C for 30 minutes while stirring. The resulting reaction solution was cooled to room temperature. As a result, ZnCdSe quantum dots were obtained in the reaction solution.

[0079] The obtained reaction solution was measured using a fluorescence spectrometer and a quantum efficiency measurement system. As a result, optical characteristics such as a fluorescence wavelength of about 490 nm, a fluorescence half-width of about 20 nm, and a quantum yield of 53% were obtained, as shown in Figure 3. In addition, in the amounts of zinc compound and cadmium compound added, the molar ratio of the amount of zinc substance to the amount of cadmium substance (Zn / Cd ratio) was 20.

[0080] The reaction solution obtained was measured using an XRD device. The results are shown in Figure 8. A scanning electron microscope (SEM) photograph of the reaction solution obtained is shown in Figure 13. The average particle size was found to be 5.8 nm. It was found that the average particle size in Example 1 and Example 2 was similar, but the fluorescence wavelengths were different. This suggests that the fluorescence wavelength changes depending on the composition.

[0081] [Example 3] 91 mg of anhydrous copper acetate (Cu(OAc)2), 4.8 mL of oleylamine (OLAm), and 7.75 mL of octadecene (ODE) were placed in a 100 mL reaction vessel, and the mixture was heated at 150°C for 5 minutes under an inert gas (N2) atmosphere with stirring to dissolve the raw materials.

[0082] To this solution, 1.4 mL of a 0.285 M solution obtained by dissolving selenium (Se) powder in dodecanethiol (DDT) and oleylamine (OLAm) was added, and the mixture was heated with stirring at 150° C. for 10 minutes. The resulting reaction solution was cooled to room temperature.

[0083] Then, 504 mg of zinc chloride (ZnCl2), 147.9 mg of cadmium acetate dihydrate (Cd(OAc)2·2H2O), 10 mL of trioctylphosphine (TOP), and 0.4 mL of oleylamine (OLAm) were added and heated with stirring at 180°C for 30 minutes under an inert gas (N2) atmosphere. The resulting reaction solution was cooled to room temperature.

[0084] Toluene and ethanol were added to this reaction solution to generate a precipitate, which was then centrifuged to recover the precipitate, and 12 ml of octadecene (ODE) was added to disperse the precipitate.

[0085] Then, 504 mg of zinc chloride (ZnCl2), 5 mL of trioctylphosphine (TOP), and 0.5 mL of oleylamine (OLAm) were added, and the mixture was heated under inert gas (N2) atmosphere at 180°C for 30 minutes while stirring. The resulting reaction solution was cooled to room temperature. As a result, ZnCdSe quantum dots were obtained in the reaction solution.

[0086] The obtained reaction solution was measured using a fluorescence spectrometer and a quantum efficiency measurement system. As a result, optical characteristics such as a fluorescence wavelength of about 510 nm, a fluorescence half-width of about 22 nm, and a quantum yield of 56% were obtained, as shown in Figure 4. In addition, in the amounts of zinc compound and cadmium compound added, the molar ratio of the amount of zinc substance to the amount of cadmium substance (Zn / Cd ratio) was 13.

[0087] The reaction solution obtained was measured using an XRD device. The results are shown in Figure 9. A scanning electron microscope (SEM) photograph of the reaction solution obtained is shown in Figure 14. The average particle size was found to be 5.8 nm. Since the average particle size in Example 3 was similar to those in Examples 1 and 2, it is believed that the fluorescence wavelength changes depending on the composition.

[0088] [Example 4] 91 mg of anhydrous copper acetate (Cu(OAc)2), 4.8 mL of oleylamine (OLAm), and 7.75 mL of octadecene (ODE) were placed in a 100 mL reaction vessel, and the mixture was heated at 150°C for 5 minutes under an inert gas (N2) atmosphere with stirring to dissolve the raw materials.

[0089] To this solution, 1.4 mL of a 0.285 M solution obtained by dissolving selenium (Se) powder in dodecanethiol (DDT) and oleylamine (OLAm) was added, and the mixture was heated with stirring at 150° C. for 60 minutes. The resulting reaction solution was cooled to room temperature.

[0090] Then, 504 mg of zinc chloride (ZnCl2), 197.2 mg of cadmium acetate dihydrate (Cd(OAc)2·2H2O), 10 mL of trioctylphosphine (TOP), and 0.4 mL of oleylamine (OLAm) were added and heated with stirring at 180°C for 30 minutes under an inert gas (N2) atmosphere. The resulting reaction solution was cooled to room temperature.

[0091] Toluene and ethanol were added to this reaction solution to generate a precipitate, which was then centrifuged to recover the precipitate, and 12 ml of octadecene (ODE) was added to disperse the precipitate.

[0092] Then, 504 mg of zinc chloride (ZnCl2), 5 mL of trioctylphosphine (TOP), and 0.5 mL of oleylamine (OLAm) were added, and the mixture was heated under inert gas (N2) atmosphere at 180°C for 30 minutes while stirring. The resulting reaction solution was cooled to room temperature. As a result, ZnCdSe quantum dots were obtained in the reaction solution.

[0093] The obtained reaction solution was measured using a fluorescence spectrometer and a quantum efficiency measurement system. As a result, optical characteristics such as a fluorescence wavelength of about 532 nm, a fluorescence half-width of about 23 nm, and a quantum yield of 52% were obtained, as shown in Figure 5. In addition, in the amounts of zinc compound and cadmium compound added, the molar ratio of the amount of zinc substance to the amount of cadmium substance (Zn / Cd ratio) was 10.

[0094] The reaction solution obtained was measured using an XRD device. The results are shown in Figure 10. A scanning electron microscope (SEM) photograph of the reaction solution obtained is shown in Figure 15. The average particle size was found to be 7.3 nm. Since the average particle size in Example 4 was similar to those in Examples 1 to 3, it is believed that the fluorescence wavelength changes depending on the composition.

[0095] [Example 5] 91 mg of anhydrous copper acetate (Cu(OAc)2), 4.8 mL of oleylamine (OLAm), and 7.75 mL of octadecene (ODE) were placed in a 100 mL reaction vessel, and the mixture was heated at 150°C for 5 minutes under an inert gas (N2) atmosphere with stirring to dissolve the raw materials.

[0096] To this solution, 1.4 mL of a 0.285 M solution obtained by dissolving selenium (Se) powder in dodecanethiol (DDT) and oleylamine (OLAm) was added, and the mixture was heated with stirring at 150° C. for 10 minutes. Then, 0.5 mL of a 0.1 M solution obtained by dissolving sulfur (S) powder in dodecanethiol (DDT) and oleylamine (OLAm) was added, and the mixture was heated with stirring at 150° C. for 5 minutes. The resulting reaction solution was cooled to room temperature.

[0097] Then, 504 mg of zinc chloride (ZnCl2), 147.9 mg of cadmium acetate dihydrate (Cd(OAc)2·2H2O), 10 mL of trioctylphosphine (TOP), and 0.4 mL of oleylamine (OLAm) were added and heated with stirring at 180°C for 30 minutes under an inert gas (N2) atmosphere. The resulting reaction solution was cooled to room temperature.

[0098] Toluene and ethanol were added to this reaction solution to generate a precipitate, which was then centrifuged to recover the precipitate, and 12 ml of octadecene (ODE) was added to disperse the precipitate.

[0099] Then, 504 mg of zinc chloride (ZnCl2), 5 mL of trioctylphosphine (TOP), and 0.5 mL of oleylamine (OLAm) were added, and the mixture was heated under inert gas (N2) atmosphere at 180°C for 30 minutes while stirring. The resulting reaction solution was cooled to room temperature. As a result, ZnCdSeS quantum dots were obtained in the reaction solution.

[0100] The reaction solution thus obtained was measured using a fluorescence spectrometer and a quantum efficiency measurement system. As a result, as shown in FIG. 6, optical characteristics were obtained, such as a fluorescence wavelength of about 477 nm and a fluorescence half-width of about 22 nm.

[0101] In Example 5, when the copper chalcogenide precursor was synthesized, two types of anion species, selenium and sulfur, were present, and the molar ratio of the amount of sulfur substance to the amount of selenium substance (S / Se ratio) was 0.125. In addition, in the amounts of zinc compound and cadmium compound added, the molar ratio of the amount of zinc substance to the amount of cadmium substance (Zn / Cd ratio) was 13.

[0102] The reaction solution obtained was measured using an XRD device. The results are shown in Figure 11. A scanning electron microscope (SEM) photograph of the reaction solution obtained is shown in Figure 16. The average particle size was found to be 5.5 nm. Since the average particle size of Example 5 was similar to those of Examples 1 to 5, it is believed that the fluorescence wavelength changes depending on the composition.

[0103] [Comparative Example 1] 91 mg of anhydrous copper acetate (Cu(OAc)2), 4.8 mL of oleylamine (OLAm), and 7.75 mL of octadecene (ODE) were placed in a 100 mL reaction vessel, and the mixture was heated at 150°C for 5 minutes under an inert gas (N2) atmosphere with stirring to dissolve the raw materials.

[0104] To this solution, 1.4 mL of a 0.285 M solution obtained by dissolving selenium (Se) powder in dodecanethiol (DDT) and oleylamine (OLAm) was added, and the mixture was heated with stirring at 150° C. for 10 minutes. The resulting reaction solution was cooled to room temperature.

[0105] Then, 98.6 mg of cadmium acetate dihydrate (Cd(OAc)2·2H2O), 10 mL of trioctylphosphine (TOP), and 0.4 mL of oleylamine (OLAm) were added, and the mixture was heated with stirring at 180°C for 30 minutes under an inert gas (N2) atmosphere. The resulting reaction solution was cooled to room temperature.

[0106] Toluene and ethanol were added to this reaction solution to generate a precipitate, which was then centrifuged to recover the precipitate, and 12 ml of octadecene (ODE) was added to disperse the precipitate.

[0107] Then, 504 mg of zinc chloride (ZnCl2), 5 mL of trioctylphosphine (TOP), and 0.5 mL of oleylamine (OLAm) were added, and the mixture was heated with stirring at 180°C for 30 minutes under an inert gas (N2) atmosphere. The resulting reaction solution was cooled to room temperature. The resulting reaction solution was measured with a fluorescence spectrometer, but no luminescence was observed.

[0108] [Comparative Example 2] A 100 mL reaction vessel was charged with 98.6 mg of cadmium acetate dihydrate (Cd(OAc)2·2H2O), 4.8 mL of oleylamine (OLAm), and 7.75 mL of octadecene (ODE). The mixture was heated to 150°C for 5 minutes under an inert gas (N2) atmosphere with stirring to dissolve the raw materials.

[0109] To this solution, 1.4 mL of a 0.285 M solution obtained by dissolving selenium (Se) powder in dodecanethiol (DDT) and oleylamine (OLAm) was added, and the mixture was heated with stirring at 150° C. for 10 minutes. The resulting reaction solution was cooled to room temperature.

[0110] Then, 504 mg of zinc chloride (ZnCl2), 10 mL of trioctylphosphine (TOP), and 0.4 mL of oleylamine (OLAm) were added, and the mixture was heated with stirring at 180°C for 30 minutes under an inert gas (N2) atmosphere. The resulting reaction solution was cooled to room temperature.

[0111] Toluene, ethanol and methanol were added to this reaction solution to generate a precipitate, which was then centrifuged to recover the precipitate, and 12 ml of octadecene (ODE) was added to disperse the precipitate.

[0112] Then, 504 mg of zinc chloride (ZnCl2), 5 mL of trioctylphosphine (TOP), and 0.5 mL of oleylamine (OLAm) were added, and the mixture was heated with stirring at 180°C for 30 minutes under an inert gas (N2) atmosphere. The resulting reaction solution was cooled to room temperature. The reaction solution was measured using a fluorescence spectrometer, and the optical characteristics were a fluorescence wavelength of about 512 nm and a fluorescence half-width of about 40 nm.

[0113] [Comparative Example 3] In a 100mL reaction vessel, 91mg of anhydrous copper acetate (Cu(OAc)2), 197.2mg of cadmium acetate dihydrate (Cd(OAc)2·2H2O), 4.8mL of oleylamine (OLAm), and 7.75mL of octadecene (ODE) were placed and heated at 150℃ for 5 minutes under an inert gas (N2) atmosphere with stirring to dissolve the raw materials.

[0114] To this solution, 1.4 mL of a 0.285 M solution obtained by dissolving selenium (Se) powder in dodecanethiol (DDT) and oleylamine (OLAm) was added, and the mixture was heated with stirring at 150° C. for 30 minutes. The resulting reaction solution was cooled to room temperature.

[0115] Then, 504 mg of zinc chloride (ZnCl2), 10 mL of trioctylphosphine (TOP), and 0.4 mL of oleylamine (OLAm) were added, and the mixture was heated with stirring at 180°C for 30 minutes under an inert gas (N2) atmosphere. The resulting reaction solution was cooled to room temperature.

[0116] Toluene, ethanol and methanol were added to this reaction solution to generate a precipitate, which was then centrifuged to recover the precipitate, and 12 ml of octadecene (ODE) was added to disperse the precipitate.

[0117] Then, 504 mg of zinc chloride (ZnCl2), 5 mL of trioctylphosphine (TOP), and 0.5 mL of oleylamine (OLAm) were added, and the mixture was heated with stirring at 180°C for 30 minutes under an inert gas (N2) atmosphere. The resulting reaction solution was cooled to room temperature. The reaction solution was measured using a fluorescence spectrometer, and the optical characteristics were a fluorescence wavelength of about 542.5 nm and a fluorescence half-width of about 52 nm.

[0118] The compositions, average particle sizes, fluorescence wavelengths, fluorescence half-widths, and fluorescence quantum yields (QY) of the above-mentioned Examples 1 to 5 and Comparative Examples 1 to 3 are summarized in the following Table 1. All composition values ​​are in mmol.

[0119] [Table 1]

[0120] As shown in Table 1, in this embodiment, the fluorescence half-width was 35 nm or less. It was also found that the fluorescence half-width could be reduced to 32 nm or less, and that in the case of ZnCdSe quantum dots or ZnCdSeS quantum dots, the fluorescence half-width could be reduced to 25 nm or less, and furthermore, that it was possible to control it to 20 nm or less. On the other hand, in the comparative examples, Comparative Example 2 and Comparative Example 3, which showed fluorescence, the fluorescence half-width was 40 nm or more, and it was found that a narrow fluorescence half-width could not be obtained.

[0121] Furthermore, as shown in Table 1, in the examples, it was found that the fluorescent wavelength could be adjusted within the range of 400 nm to 700 nm. It was also found that the fluorescent wavelength could be adjusted within the range of 450 nm to 700 nm.

[0122] Furthermore, as shown in Table 1, it was found that in the examples, the average particle size of the quantum dots could be adjusted within the range of 2 nm to 10 nm. Furthermore, the particle sizes of 95% or more of the quantum dots were within the range of ±2 nm of the average particle size, and it was found that a large number of quantum dots could be produced with extremely uniform particle sizes.

[0123] Furthermore, the quantum dot particle dispersions of Examples 1 to 5 were measured using an X-ray diffraction (XRD) device and a scanning electron microscope (SEM). Figures 7 to 11 show the measurement results using the X-ray diffraction (XRD) device, and Figures 12 to 16 show the measurement results using the scanning electron microscope (SEM).

[0124] In addition to Example 1 (CdSe quantum dots), the XRD spectrum of ZnSe particles as quantum dots after cation exchange is also shown for reference in Figure 7. As shown in Figure 7, it was confirmed that the peak values ​​of Example 1 and ZnSe were different.

[0125] Also, it was confirmed that the peak value of the XRD spectrum of the ZnCdSe quantum dots shown in Figures 8 to 10 differs depending on the amount of Cd used. That is, as shown in Table 1, it was found that the peak value of the XRD spectrum differs in Examples 2 to 4 due to the different composition ratios of the cationic species Zn and Cd. Also, the peak value of the XRD spectrum shown in Figure 9 of Example 3 differs from the peak value of the XRD spectrum shown in Figure 11 of Example 5 in which sulfur (S) is added to Example 3, and this confirmed that the peak value of the XRD spectrum differs due to the addition of sulfur (S).

[0126] As shown in each example, it was found that by adjusting the ratio of cadmium and zinc added as cationic species in the metal substitution method, it is possible to control the fluorescence wavelength of the quantum dots in the range of 400 nm or more and 700 nm or less while maintaining the fluorescence half-width at 35 nm or less.

[0127] Specifically, in this embodiment, it was found that by adjusting the molar ratio of zinc to cadmium within a range of 30 or less, the fluorescence wavelength of the quantum dots can be freely adjusted within a range of 400 nm or more and 700 nm or less while maintaining the fluorescence half-width of the quantum dots at 35 nm or less.

[0128] Furthermore, as shown in each example, it was found that by adjusting the ratio of selenium and sulfur added as anion species when synthesizing the copper chalcogenide precursor, it is possible to control the fluorescence wavelength in the range of 400 nm or more and 700 nm or less while maintaining the fluorescence half-width of the quantum dots at 32 nm or less.

[0129] Specifically, in this embodiment, it was found that by adjusting the molar ratio of sulfur to selenium in the range of 0.2 or less, the fluorescence wavelength of the quantum dots can be freely adjusted in the range of 400 nm or more and 700 nm or less while maintaining the fluorescence half-width of the quantum dots at 35 nm or less. [Industrial Applicability]

[0130] According to the present invention, Cd-based quantum dots that emit blue to red fluorescence can be stably obtained. By applying the quantum dots of the present invention to LEDs, backlight devices, display devices, etc., excellent light emission characteristics can be obtained in each device. [Explanation of symbols]

[0131] 1: Quantum dots 1a: Core 1b: Shell 2 :Organic ligand

Claims

1. Cu as a precursor is prepared from an organic copper compound or an inorganic copper compound and an organic chalcogen compound. 2 Se or Cu 2 Synthesize SeS, Zinc compound and cadmium compound are added simultaneously to form Cu 2 Se or Cu 2 Metal exchange of the copper of SeS with cadmium and zinc; The Zn / Cd molar ratio is CdZnSe having a molar ratio of 10 to 20, or the Zn / Cd molar ratio is CdZnSeS having a molar ratio of 10 to 20 and a molar ratio of S / Se of more than 0 to 0.2, A method for producing quantum dots, comprising synthesizing quantum dot cores having a fluorescence half-width of 35 nm or less and an average particle size of 2 nm to 10 nm.

2. 2. The method for producing quantum dots according to claim 1, wherein the particle size of the precursor is within a range of ±2 nm of the average particle size.

3. 3. The method for producing quantum dots according to claim 1, wherein the ratio of cadmium and zinc added as cationic species in the metal substitution method is adjusted to control the fluorescence wavelength of the quantum dots to within a range of 400 nm to 700 nm while maintaining the fluorescence half-width of the quantum dots to 35 nm or less.

4. A method for producing quantum dots described in any one of claims 1 to 3, characterized in that the ratio of selenium and sulfur added as anion species when synthesizing the precursor is adjusted to control the fluorescence wavelength of the quantum dots to be within the range of 400 nm or more and 700 nm or less while maintaining the fluorescence half-width of the quantum dots to be 35 nm or less.

5. 5. The method for producing quantum dots according to claim 1, wherein the metal exchange reaction is carried out at a temperature of 140° C. or higher and 300° C. or lower.

6. 6. The method for producing quantum dots according to claim 1, wherein the precursor is synthesized at a reaction temperature of 120° C. or higher and 250° C. or lower.

7. A precursor, Cu2Se or Cu2SeS, is synthesized from an organic copper compound or an inorganic copper compound and an organic chalcogen compound; A zinc compound and a cadmium compound are added at the same time, and the copper of Cu2Se or Cu2SeS is exchanged with the cadmium and zinc, The Zn / Cd molar ratio is CdZnSe having a molar ratio of 10 to 20, or the Zn / Cd molar ratio is CdZnSeS having a molar ratio of 10 to 20 and a molar ratio of S / Se of more than 0 to 0.2, A quantum dot core having a fluorescence half-width of 35 nm or less, an average particle size of 2 nm to 10 nm, and a quantum yield of 50% or more was synthesized. A quantum dot characterized by:

Citation Information

Patent Citations

  • Blue light core-shell quantum dot, and preparation method and application thereof

    CN111117595A

  • Luminescent material consisting of nanocrystals with core / shell structure, and method for preparing the same material

    JP2005522534A

  • CdSe QUANTUM DOT AND MANUFACTURING METHOD THEREOF

    JP2009161372A

  • METHOD FOR PRODUCING CdSe COLLOIDAL PARTICLES

    JP2017160073A

  • Quantum dots for light emission and method for synthesizing the same

    JP2017503901A